THE EFFICIENCY OF PHYSICAL THERAPY IN OPTIMIZING THE RESPIRATORY FUNCTION FOR ASTHMATIC CHILDREN - Rata Marinela (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The purpose of this paper is to highlight the role of physical therapy in the field of respiratory pathology in children, mainly in bronchial asthma. By the hypothesis we want to prove that the intervention through physical therapy applied based on structured programs according to the needs of the subject and implemented by a specific methodology is able to optimize the functionality of asthmatic children. Material. The subjects of the study were three in number, aged 4-6 years, diagnosed with infantile asthma around the age of three years old. The experimental methods were selected based on objective clinical and functional assessment and intervention methods were chosen according with specific objectives, exemplifying respiratory exercises, games with objects and equipment, respiratory flow modulation techniques. Sessions were conducted three times a week totaling an amount of 36 sessions over three months. We obtained favorable results for all evaluated parameters, which were also influenced by the severity and number of occurrences of crises, the precocity of diagnosis and the moment when the treatment program started, the consistency of treatment sessions, the conditions of their entire activity and permanent collaboration between physician, physical therapist and parents. In conclusion, the experiment confirms the effectiveness of respiratory physiotherapy to optimize functionality in asthmatic children. Performing breathing exercises significantly reduces the occurrence of wheezing and improves effort capacity.